SISTEM PAKAR DIAGNOSIS PENYAKIT PADA TANAMAN JAGUNG DENGAN METODE FORWARD CHAINING BERBASIS WEB - Asnawati; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2025)
Technology is used in the form of business to make decisions in solving problems. One form of utilizing information technology is an expert system. Seeing the many benefits of corn, and the increasing demand for corn production, many farmers are cultivating corn plants which are considered to be a business opportunity for farmers. The source of problems often experienced by farmers is that corn plants are easily attacked by plant diseases which can attack at any time. To overcome and reduce this risk, farmers need to take appropriate action in maintaining these plants. However, currently there is still a lack of knowledge from expert farmers in dealing with disease attacks to determine the appropriate treatment for infected corn plants. As a result of delays in handling, corn farmers often experience significant losses, some even have crop failures. To achieve this goal, a problemsolving method is needed, namely using the forward chaining method, where this method is a search method that obtains accurate results based on known facts which are then matched with existing facts so as to find valid data and lead to a final decision.